1996
DOI: 10.1111/j.1365-2338.1996.tb01511.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of different methods for the detection of Ralstonia solanacearum in potato tuber extracts

Abstract: The sensitivities of various methods for the detection of Ralstonia solanacearum following dilution in healthy potato tuber tissue macerate were compared. Estimated pathogen populations in undiluted macerates, from samples of 200 heel‐end vascular cores each containing a single diseased and 199 healthy tubers, ranged from 1.2 × 106–7.4 × 107 colony‐forming units per ml. Following concentration by high‐speed centrifugation and resuspension in phosphate buffer, the pathogen was detected by all methods studied, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
215
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(222 citation statements)
references
References 12 publications
4
215
0
3
Order By: Relevance
“…For each IGC time point, 3 plants were collected in the order they were placed in the tray and pooled; this procedure was repeated three times. The IGC was performed as described (52), except that 5 l of the diluted solutions were spotted on SMSA plates (53). The typical R. solanacearum phenotype of the bacteria counted on the different dilutions was checked on B rich medium.…”
Section: Methodsmentioning
confidence: 99%
“…For each IGC time point, 3 plants were collected in the order they were placed in the tray and pooled; this procedure was repeated three times. The IGC was performed as described (52), except that 5 l of the diluted solutions were spotted on SMSA plates (53). The typical R. solanacearum phenotype of the bacteria counted on the different dilutions was checked on B rich medium.…”
Section: Methodsmentioning
confidence: 99%
“…Stems from wilted plants were cut at different levels above the inoculation point and segments of 2-3 cm were analysed for presence of R. solanacearum. Extracts were plated onto a modified semiselective medium South Africa (SMSA) agar (Elphinstone et al, 1996) and colonies were PCRtested (OLI1 Y2 primers) as described in EU Directives (Anonymous, 1998(Anonymous, , 2006. Stems from inoculated non-wilted plants were processed in the same way after 6 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Seal et al (1993) reported that PCR can detect as few as one to ten R. solanacearum cells, although this level of sensitivity could not be reproduced by other workers (Elphinstone et al, 1996;Martins, 2000). New methods have produced an increase in the sensitivity of detection techniques, an example being the use of a pretreatment protocol involving semi-selective enrichment medium plus the addition of 0.05 M NaOH and heating at 100 °C for 6 minutes during the PCR (Elphinstone et al, 1996). Martins (2000) determined the sensitivity of the PCR technique for potato tuber samples as being 3.7 x 10 3 CFU mL -1…”
Section: Detection Of Ralstonia Solanacearum In Tubers Of Asymptomatimentioning
confidence: 91%
“…However, some tubers were positive for R. solanacearum by DAS-ELISA and PCR, indicating the latent nature of the infection in resistant genotypes as well as in susceptible ones (Table 4) Using the same DNA extraction method and primers (Oli 1 and Y2) as were used by us, Llop et al (1999) found that PCR was more efficient at detecting latent infections of potato tubers as compared to ELISA and immunofluorescence tests using polyclonal anti-sera or traditional microbiological methods, with PCR being able to detect as few as 100 colony forming units (CFU).mL aimed at minimizing dissemination of the pathogen through infected tubers (Elphinstone et al, 1996;Priou et al, 1999;Llop et al, 1999;Martins, 2000). Seal et al (1993) reported that PCR can detect as few as one to ten R. solanacearum cells, although this level of sensitivity could not be reproduced by other workers (Elphinstone et al, 1996;Martins, 2000). New methods have produced an increase in the sensitivity of detection techniques, an example being the use of a pretreatment protocol involving semi-selective enrichment medium plus the addition of 0.05 M NaOH and heating at 100 °C for 6 minutes during the PCR (Elphinstone et al, 1996).…”
Section: Detection Of Ralstonia Solanacearum In Tubers Of Asymptomatimentioning
confidence: 99%